Strain difference in the effect of infralimbic cortex lesions on fear extinction in rats - Chang, Chun-hui (2010)
The infralimbic division of the medial prefrontal cortex (IL) has been implicated in the consolidation and retention of extinction memories. However, the effects of IL lesions on the retention of extinction memory are inconsistent. In the present experiments, we examined whether rat strain influences the effects of IL lesions on extinction. In Experiment 1, Sprague-Dawley (SD) or Long-Evans (LE) rats received a standard auditory fear conditioning procedure, which was followed by an extinction session; freezing served as the index of conditional fear. Our results reveal that focal IL lesions impair the retention of extinction in SD, but not LE rats. In addition to the strain difference in sensitivity to IL lesions, LE rats exhibited significantly higher levels of contextual fear before the outset of extinction training than SD rats. In a second experiment we thus examined whether contextual fear influenced the sensitivity of extinction to IL lesions in LE rats. Long-Evans rats received the same conditioning as in Experiment 1, and then were either merely exposed to a novel context or administered unsignaled shocks in that context, followed by extinction and test sessions. Our results reveal that LE rats with IL lesions showed normal extinction regardless of the levels of contextual fear manifest before extinction. Thus, we conclude that rat strain is an important variable that influences the role of infralimbic cortex in fear extinction.